2012
DOI: 10.1039/c2jm16006d
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalently modified graphene sheets by imidazolium ionic liquids for multifunctional polymer nanocomposites

Abstract: Chemical reduction of graphite oxide (GO) to produce graphene nanosheets often results in irreversible agglomeration and precipitation. Herein, stable well-dispersed graphene sheets in solvents were obtained by simultaneous functionalization and reduction of GO under alkaline conditions, in the presence of sodium borohydride and imidazolium ionic liquids (Imi-ILs) containing two vinyl-benzyl groups. In this case, positively charged imidazolium groups of Imi-ILs underwent ion-exchange with negatively charged GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 73 publications
3
105
1
3
Order By: Relevance
“…to improve their dispersion in polymer matrix, which will enhance the overall performance of the nanocomposites. [7][8][9][10] Among various nano-llers, CNTs modied by using ionic liquid can be used as potential reinforcing ller in various polymer matrixes which include elastomers, thermoplastics, thermosets and polyamides.…”
Section: Introductionmentioning
confidence: 99%
“…to improve their dispersion in polymer matrix, which will enhance the overall performance of the nanocomposites. [7][8][9][10] Among various nano-llers, CNTs modied by using ionic liquid can be used as potential reinforcing ller in various polymer matrixes which include elastomers, thermoplastics, thermosets and polyamides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Han et al [61] have reported that graphene sheets are stably dispersed in an Imi-IL of 1-butyl-3-methylimidazolium hexafluorophosphate (BmimPF 6 ) with the help of poly(1-vinyl-3-butylimidazolium chloride) [poly(VbimCl)]. More recently, we have shown that Imi-ILs functionalized graphene sheets are homogenously embedded in the poly(methyl methacrylate) (PMMA) matrix and thus contribute to high electrical conductivity, low percolation threshold and large increases in storage modulus, glass transition temperature (T g ) and thermal stability compared to PMMA [62]. Over the past decade, the Imi-ILs assisted fabrication of polymer composites with CNTs and graphene has triggered an increasing attention [63]; however, a comprehensive review is still absent from the literatures.…”
Section: Introductionmentioning
confidence: 99%
“…However, bulk graphene sheets from RGO tend to restack as a graphite-like structure and show low dispersion in various solvents and polymers. Recently, we have reported a novel method to fabricate graphene/PMMA composites [62]. Initially, the functionalized graphene sheets were produced by chemical reduction of GO with NaBH 4 in the presence of NaOH and 1,6-bis[3-(vinyl benzyl)imidazolium-1-yl]hexane chloride (VbimBr) (Figure 2a).…”
Section: With Graphenementioning
confidence: 99%
“…One active field for PMMA application is the incorporation of nanomaterials. Over the past decade, many reports have been published on the addition of functionalized graphene sheets (FGSs) to PMMA to impart a variety of improved physical properties [13][14][15][16][17][18][19][20][21]. Villar-Rodil et al [16] prepared chemically reduced graphene/ PMMA by free radical solution-polymerization of methyl methacrylate (MMA) in the presence of exfoliated graphene oxide (GO).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the glass transition temperature shifted by over 15°C with graphene loadings as low as 0.05 wt%, and the elastic modulus increased by 28% at just 1 wt% loading. Jang et al [18] prepared conductive composites of PS/PMMA blends filled with octadecylamine-functionalized graphene (GE-ODA) and studied the electrical properties. Their results imply that the incorporation of GE-ODA into immiscible polymer blends is an efficient means of improving the electrical properties.…”
Section: Introductionmentioning
confidence: 99%